(untitled) (Revista de História da UEG (REVHIST), 2020)
This paper proposes a brief discussion about the insertion of northeastern migrants in the peripheral region of a small municipality located in the northeast of the state of São Paulo (Orlândia). For this, this text will use analyzes that are under development on this theme, in particular, we will highlight the processes of segregation and stigmatization of northeastern migrants from their relationship / contact with local residents (paulistas / orlandinos) in the region neighborhood (José Vieira Brazão and Jardim Santa Rita) in the municipality of Orlândia-SP. Keywords: Migration. Periphery. Northeast. Paulistas.